Zimbabwe dollarisation: short term gift, long term curse - reintroducing the Zimbabwe dollar using the gold standard - Ushewokunze, Mutemwa Tendayi (Research of GSB, 2018)
Historical analysis suggests that in the short to medium term, dollarization as a monetary policy measure, post a period of high inflation, reduces economic volatility, stabilises the inflation of goods and services, and restores economic predictability. However, in fully dollarized economics (as opposed to dual currency economies,) in the medium term, the effects of dollarization do not create a suitable environment for long term sustainable growth. This paper discusses the benefits and challenges of full dollarization and suggests a further policy measure of re-introducing the local currency through a managed regime. The paper looks to smoothing out money supply volatility through Zimbabwe dollar introduction. Understanding the responsiveness of the economy to monetary liquidity is explained through theoretical and extrapolative statistical analysis derived from a short-range historic time series.